Illocution and Perlocutionary Effects in the Novel Namaku Alam by Leila S. Chudori - Dyah Utari, Lintang; Wahdah Humaira, Hera; Setiadi, David (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research departs from the need to understand speech acts in the realm of written language. The speech acts that become the focus of the research are illocution and their perlocutionary effects. The purpose of the research is to examine the forms of illocution and perlocutionary effects that appear in the novel Namaku Alam by Leila S. Chudori as well as to understand how speech acts are contained in the dialogue of the novel. This research uses a descriptive qualitative method with listening or reading and note-taking techniques as the technique of data collection. The data taken are focused on dialogues related to the impact of the 1965 tragedy experienced by the main character. The results of the analysis will be described in detail to illustrate the findings. The pragmatic approach becomes the basis of analysis, with the theory of illocution by Searle and Austin which includes assertive, directive, expressive, commissive and declarative illocution as well as the theory of perlocution by Kartika and Widodo, namely perlocution of positive response, negative response and nonresponse as references. The results of the research produce 28 data with details of 15 illocution data divided into five categories, namely 4 assertive data, 4 directive data, 4 expressive data, 1 commissive data, and 1 declarative data, as well as 15 perlocution data consisting of 4 positive response data, 9 negative response data, and 1 nonresponse data. The overall findings show that the novel functions not only as a literary work, but also as a medium that reflects the complexity of communicative interaction.